Students’ Perception of the Daily English Songs Program in Pesantren Walisongo Ngabar Female Campus - Arifah, Nesa Nur; Virgiyanti, Diska Fatima; Munif, Dian Nashrul (Journal of Nusantara Education, 2026)
This study explores students’ perceptions of the Daily English Songs program at Pesantren Walisongo Ngabar Female Campus during the 2024/2025 academic year. It addresses the need for effective, contextually relevant strategies to strengthen English proficiency within an Islamic boarding school environment in which global communication skills must be balanced with religious education. A descriptive qualitative design was employed, involving ten students from grades one through six selected via purposive sampling. Data were collected through interviews and observations. The analysis followed the Miles and Huberman framework, consisting of data reduction, data display, and conclusion drawing/verification. Findings indicate that the program is an engaging method for supporting language learning. Students perceived the songs as effective tools for enhancing vocabulary acquisition, improving pronunciation, and providing entertainment to alleviate the monotony of dormitory life. While positive perceptions dominated, some students reported boredom due to the repetitive playback of the same songs, suggesting a need for more frequent rotation of material. The outcomes underscore the importance of creative educational media in a pesantren setting. By using songs with Islamic themes, the program successfully integrates international language mastery without compromising spiritual values. The study concludes that daily exposure to English music facilitates natural language internalization and increases students’ motivation.